Administrative theory in transition - Griffiths, Daniel E. (Deakin University, 2020)
This book forms part of the Theory and practice in educational administration course offered by the School of Education in Deakin University's Open Campus Program. It has been prepared in collaboration with the Theory and practice in educational administration course team